Micropropagation of Alocasia amazonica through Indirect Shoot Organogenesis (Plant Tissue Culture and Biotechnology, 2022)
The present experiment was conducted to establish an efficient in vitro regeneration protocol for Alocasia amazonica through indirect organogenesis from young leaf segment. For callus induction, leaf explants were inoculated on MS medium containing different concentrations of 2,4-D. Highest callus induction frequency (90%) was recorded on MS medium supplemented with 4.0 mg/l 2,4-D. Remarkable results on indirect shoot organogenesis and multiplication (86.67%) with maximum shoot number per unit callus (11.64 ± 0.37) and shoot length (10.13 ± 0.24 cm) were observed when the leaf derived callus were transferred on MS medium fortified with 1.5 mg/l BAP and 0.5 mg/l NAA. Additionally, the incorporation of 10% coconut water with the medium showed satisfactory shoot growth and development. The best response towards root induction (85%) was achieved on ½ MS medium fortified with 3.0 mg/l IBA, 2.0 mg/l IAA and 2.0 mg/l NAA with an average 22.20 ± 0.87 roots per unit shoot. Well rooted plantlets were successfully acclimatized to the soil where the survival rate was 90%.Plant Tissue Cult. & Biotech. 32(1): 13-20, 2022 (June)